CO2 separation membrane with high permeability coefficient as well as preparation method and application of CO2 separation membrane

By using polypropylene carbonate and polyhexadioic acid/butylene terephthalate as the materials for the CO2 separation membrane, the permeability coefficient and selectivity of CO2 are improved, and the problem of high recovery cost of high flow and low concentration CO2 in the prior art is solved, and efficient and economical CO2 separation effect is achieved.

CN119607928AActive Publication Date: 2025-03-14HUAFON GROUP

Patent Information

Application Number
CN202411883131.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-14
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing CO2 separation membranes require a large membrane area in the recovery of large flow and low concentration CO2, resulting in high recovery costs and low permeability coefficient of CO2, making it difficult to meet the needs of efficient separation.

Method used

Polypropylene carbonate (PPC) and polyhexachloric acid/butylene terephthalate (PBAT) are used as important components of the separation membrane. By adjusting the material content and molecular structure, the permeability of CO2 and the selectivity of CO2/N2 are improved.

Benefits of technology

The high permeability coefficient of the CO2 separation membrane is achieved, reaching more than 35,000 Bar, and maintaining high CO2/N2 selectivity. It is suitable for purification and separation of large flow and low concentration CO2, reducing recycling costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a CO2 separation membrane with a high permeability coefficient and a preparation method and application thereof.The CO2 separation membrane is prepared from raw materials including polypropylene carbonate and polyadipic acid / butylene terephthalate, and by taking the total weight of the raw materials of the CO2 separation membrane as 100%, the content of polypropylene carbonate accounts for 70-95 wt%, the content of polyadipic acid accounts for 10-20 wt%, and the content of polyadipic acid accounts for 10-20 wt%. The content ratio of the polyadipic acid / butylene terephthalate is 4 to 30 percent. The CO2 permeability coefficient of the separation membrane can reach 35000 Bar (25 DEG C / 0.1 MPa) or above, the CO2 / N2 selectivity is 10-20, and the separation membrane is suitable for purification and separation of high-flow and low-concentration CO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas separation membranes and relates to a CO2 separation membrane with a high permeability coefficient and a preparation method and application thereof. Background Art

[0002] With the development of society, the total emission of CO2 is increasing year by year, and the capture and recovery of CO2 is imperative, and membrane separation is one of the most promising CO2 recovery technologies. Commonly used membrane materials include polyimide, polysulfone, polysiloxane, polyethylene oxide and polyether block amide, etc. The above materials have high selectivity for CO2 / N2, but due to the limitation of the material structure itself, the permeability coefficient of CO2 is generally between 1000 and 5000 Bar (25℃ / 0.1MPa). For the recovery of large flow and low concentration CO2 (such as the capture of CO2 in flue gas), the use of this type of membrane material requires a large membrane area, which greatly increases the recovery cost. Therefore, it is urgent to develop a CO2 separation membrane with high permeability. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a CO2 separation membrane with a high permeability coefficient and a preparation method and application thereof. The CO2 permeability coefficient of the separation membrane of the present invention can reach 35000Bar (25℃ / 0.1MPa), and the CO2 / N2 selectivity is 10-20, which is suitable for large flow and low concentration CO2 purification and separation.

[0004] To achieve this object, the present invention adopts the following technical solutions:

[0005] On the one hand, the present invention provides a CO2 separation membrane with a high permeability coefficient. The raw materials for preparing the CO2 separation membrane include polypropylene carbonate (PPC) and polybutylene adipate / terephthalate (PBAT). Based on the total weight of the raw materials for preparing the CO2 separation membrane as 100%, the content of polypropylene carbonate accounts for 70 to 95wt%, and the content of polybutylene adipate / terephthalate accounts for 4 to 30%.

[0006] In the present invention, by selecting polypropylene carbonate and polybutylene adipate / terephthalate as important components of the separation membrane, the separation membrane can significantly improve the permeability coefficient of CO2 and has a higher CO2 / N2 selectivity.

[0007] In the present invention, PBAT can effectively improve the toughness of the separation membrane and has a processing temperature similar to that of PPC, so PBAT is selected for addition. If PLA is selected, wrinkles are easily generated on the membrane surface, affecting the appearance and use, while PHA and PBA are too expensive.

[0008] In the present invention, the number average molecular weight Mn of the polypropylene carbonate is 30000-200000 g / mol, for example, 30000 g / mol, 50000 g / mol, 80000 g / mol, 100000 g / mol, 120000 g / mol, 150000 g / mol, 180000 g / mol or 200000 g / mol, and the PDI (molecular weight distribution) is 2-6, for example, 2, 2.2, 2.5, 2.8, 3, 3.3, 3.5, 3.8, 4, 4.3, 4.5, 4.8, 5, 5.2, 5.5, 5.7 or 6, etc.

[0009] Preferably, the polypropylene carbonate has a propylene carbonate content of less than 2 wt%, such as 2 wt%, 1.8 wt%, 1.5 wt%, 1.3 wt%, 1 wt%, 0.8 wt%, 0.5 wt%, 0.3 wt% or 0.1 wt%.

[0010] Preferably, the glass transition temperature of the polypropylene carbonate is 24-36°C, for example, 24°C, 28°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C or 36°C.

[0011] Preferably, the polypropylene carbonate is obtained by reacting propylene oxide (PO) and CO2 as raw materials in the presence of a catalyst. Preferably, the reaction temperature is 50-90°C (e.g., 50°C, 53°C, 55°C, 58°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C), and the reaction time is 5-20h (e.g., 5h, 8h, 10h, 12h, 15h, 18h or 20h); preferably, the reaction is carried out at a pressure of 1.0-6.0MpaG (e.g., 1.0MPaG, 1.3MPaG, 1.5MPaG, 2MPaG, 2.5MPaG, 3MPaG, 3.5MPaG, 4MPaG, 4.5MPaG, 5MPaG, 5.5MPaG or 6MPaG).

[0012] Preferably, the catalyst includes but is not limited to any one or a combination of at least two of zinc carboxylates, rare earth complexes, alkyl zincs, double metal cyanides, metal porphyrins, β-diimines or Salen complexes.

[0013] Preferably, the reaction is carried out in a solvent, and the solvent is selected from a polar aprotic solvent with low electron donating capacity, including but not limited to any one of PO (propylene oxide), supercritical CO2, dichloromethane, chloroform, acetone, toluene or dimethyl sulfoxide, or a combination of at least two thereof.

[0014] Preferably, the melt index of the polybutylene adipate / terephthalate at 190° C. and 2.16 kg is 3 to 5 g / 10 min, for example, 3 g / 10 min, 3.5 g / 10 min, 3.8 g / 10 min, 4 g / 10 min, 4.5 g / 10 min, 4.8 g / 10 min or 5 g / 10 min.

[0015] Preferably, the terminal carboxyl content of the polybutylene adipate / terephthalate is not more than 25 mol / t, for example, 25 mol / t, 20 mol / t, 18 mol / t, 15 mol / t, 10 mol / t, 8 mol / t, 6 mol / t, 3 mol / t, 2 mol / t, etc.

[0016] Preferably, the water content of the polybutylene adipate / terephthalate is no more than 500 ppm, for example, 500 ppm, 450 ppm, 400 ppm, 350 ppm, 300 ppm, 200 ppm, 100 ppm, 80 ppm, 50 ppm, 30 ppm, 20 ppm, 10 ppm, 5 ppm, etc.

[0017] In the present invention, based on the total weight of the raw materials for preparing the CO2 separation membrane as 100%, the content of the polypropylene carbonate accounts for 70 to 95wt%, for example, 70wt%, 73wt%, 75wt%, 78wt%, 80wt%, 83wt%, 85wt%, 88wt%, 90wt%, 93wt% or 95wt%, and the content of the polybutylene adipate / terephthalate accounts for 4 to 30%, for example, 4wt%, 6wt%, 8wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30wt%.

[0018] Preferably, the weight ratio of polypropylene carbonate to polybutylene adipate / terephthalate is 2.5 to 4: 1, for example, 2.5: 1, 2.8: 1, 3: 1, 3.3: 1, 3.5: 1, 3.8: 1 or 4: 1. In the present invention, if the weight ratio of polypropylene carbonate to polybutylene adipate / terephthalate is less than 2.5: 1, the selectivity of the separation membrane will be significantly reduced, and if the weight ratio is greater than 4: 1, the membrane strength will be reduced.

[0019] Preferably, the raw material for preparing the CO2 separation membrane further comprises at least one of an optional compatibilizer, an optional antioxidant or an optional anti-hydrolysis agent.

[0020] Preferably, the compatibilizer includes one or a combination of at least two of ADR-4468, ADR-4368 or ADR-4385.

[0021] Preferably, the antioxidant comprises one or a combination of at least two of antioxidant-1010, antioxidant-1076, antioxidant-168, antioxidant-B215 or antioxidant-B245;

[0022] Preferably, the anti-hydrolysis agent includes one of Stabaxol I, Stabaxol P100 or Stabaxol P200, or a combination of at least two of them.

[0023] Preferably, the raw materials for preparing the high permeability CO2 separation membrane include the following components in weight percentage:

[0024] 70-95wt% of polypropylene carbonate (PPC), 4-30wt% of polybutylene adipate / terephthalate (PBAT), 0.1-2wt% of compatibilizer (e.g., 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1wt%, 1.3wt%, 1.5wt%, 1.8wt% or 2wt%), 0.1-1.5wt% (e.g., 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1wt%, 1.3wt% or 1.5wt%) of antioxidant, 0.1-1wt% (e.g., 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt% or 1wt%) of anti-hydrolysis agent.

[0025] The thickness of the high permeability CO2 separation membrane is 30-100 μm, such as 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm. If the thickness of the CO2 separation membrane is too thin, the separation membrane strength is insufficient, and if the thickness is too thick, the permeation rate will be affected.

[0026] The method for preparing the CO2 separation membrane with a high permeability coefficient can be prepared by coating, blowing, casting and the like.

[0027] On the other hand, the present invention provides a method for preparing a CO2 separation membrane with a high permeability coefficient as described above, the preparation method comprising the following steps:

[0028] Polypropylene carbonate (PPC), polybutylene adipate / terephthalate (PBAT), an optional compatibilizer, an optional antioxidant, and an optional anti-hydrolysis agent are dissolved in a solvent to obtain a solution, and the solution is coated to form a membrane to obtain the CO2 separation membrane with a high permeability coefficient.

[0029] The method utilizes a coating method to prepare the CO2 separation membrane, and the concentration of the solution as described above (referring to the total concentration of the solute) is 5 to 15wt%, for example 5wt%, 8wt%, 10wt%, 12wt%, 14wt% or 15wt%.

[0030] Preferably, the solvent is selected from any one of N,N-dimethylformamide (DMF), dichloromethane, acetone, toluene or dimethyl sulfoxide, or a combination of at least two thereof.

[0031] On the other hand, the present invention provides another method for preparing a CO2 separation membrane with a high permeability coefficient as described above, the preparation method comprising the following steps:

[0032] Polypropylene carbonate (PPC), polybutylene adipate / terephthalate (PBAT), an optional compatibilizer, an optional antioxidant and an optional anti-hydrolysis agent are mixed, melt-extruded into granules, and then blown into a film to obtain the CO2 separation membrane with a high permeability coefficient.

[0033] The present method adopts a blow molding method to prepare the separation membrane, and the processing temperature of the melt extrusion is 135-170°C, for example, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C or 170°C.

[0034] Preferably, the temperature of the film blowing is 130-170°C, for example 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C or 170°C.

[0035] On the other hand, the present invention provides another method for preparing a CO2 separation membrane with a high permeability coefficient as described above, the preparation method comprising the following steps:

[0036] Polypropylene carbonate (PPC), polybutylene adipate / terephthalate (PBAT), an optional compatibilizer, an optional antioxidant and an optional anti-hydrolysis agent are mixed, melt-extruded into granules, and then cast film or biaxially stretched film to obtain the CO2 separation membrane with a high permeability coefficient.

[0037] The method adopts a casting method or a biaxial stretching process to prepare the separation membrane, wherein the processing temperature of the melt extrusion is 135-170°C, for example, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C or 170°C.

[0038] Preferably, the film-forming by casting is carried out in a casting machine.

[0039] Preferably, the temperature of the film casting is 150-180°C, for example, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C or 180°C.

[0040] On the other hand, the present invention provides the use of the CO2 separation membrane with a high permeability coefficient as described above in CO2 capture and recovery.

[0041] In the present invention, the high permeability coefficient refers to the permeability coefficient of CO2 being above 35000 Bar.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] The present invention uses polypropylene carbonate and polybutylene adipate / terephthalate as important components of the separation membrane, wherein polypropylene carbonate contains a large amount of carbonyl groups with affinity for CO2, and PPC is an amorphous polymer, which will not cause the CO2 permeability coefficient to decrease due to crystallization; the addition of PBAT enhances the membrane toughness, enhances the permeability coefficient, and increases the service life of the separation membrane. The CO2 permeability coefficient of the separation membrane of the present invention can reach more than 35000Bar (25℃ / 0.1MPa), and the CO2 / N2 selectivity is 10-20. Under the same membrane area, the separation efficiency of the separation membrane of the present invention is higher, and it is suitable for large flow and low concentration CO2 purification and separation. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0045] The preparation methods of the materials used in the following examples and comparative examples are as follows:

[0046] PPC Preparation:

[0047] The synthesis of PPC-1 was prepared with reference to Example 10 in CN113185684A, and had a number average molecular weight of 95,000 g / mol, a PDI of 3.6, a propylene carbonate content of 0.5 wt %, and a glass transition temperature of 31°C.

[0048] The difference between the preparation of PPC-2 and that of PPC-1 is that the polymerization reaction time is adjusted from 12 h to 4 h to obtain PPC-2, whose number average molecular weight Mn is 25,000 g / mol, molecular weight distribution PDI is 5, propylene carbonate content is 3.6 wt%, and glass transition temperature is 23°C.

[0049] The preparation of PPC-3 is different from that of PPC-1 in that the polymerization reaction time is adjusted from 12 h to 5 h to obtain PPC-3, whose number average molecular weight Mn is 40,000 g / mol, molecular weight distribution PDI is 3.8, propylene carbonate content is 3.2 wt%, and glass transition temperature is 24°C.

[0050] Preparation of PPC-4: PPC-4 was obtained by referring to Example 7 of CN113185684A. The number average molecular weight Mn was 200000 g / mol, the molecular weight distribution PDI was 5.47, the propylene carbonate content was 0.4 wt%, and the glass transition temperature was 31°C.

[0051] The preparation method of PBAT is as follows:

[0052] At 120°C, terephthalic acid, adipic acid and butanediol in a molar ratio of 1:1:1.8 are dehydrated for 2 hours, then heated to 150°C, and after they are melted, a catalyst tetraisopropyl titanate (the amount used is 0.2% of the total mass of terephthalic acid, adipic acid and butanediol) is added thereto, and a first polymerization reaction is carried out at 130°C and normal pressure for 2 hours, and then the temperature is increased to 230°C at a heating rate of 30°C / h, and a second polymerization reaction is carried out at an absolute pressure of 50KPa for 2 hours, and then a third polymerization reaction is carried out at 250°C and an absolute pressure of less than 500Pa for 5 hours to obtain the biodegradable copolyester, and the product has a melt index of 3.5g / 10min, a terminal carboxyl group of 15mol / t, and a moisture content of 400ppm.

[0053] The preparation method of PBS is as follows:

[0054] Succinic acid and 1,4-butanediol in a molar ratio of 0.9:1 are mixed, and a catalyst tetraisopropyl titanate (the amount used is 0.1% of the total mass of succinic acid and 1,4-butanediol) is added, and an esterification reaction is carried out at 180° C. and normal pressure for 3 hours. The temperature is then raised to 210° C., the vacuum degree is adjusted to 5 KPa, and the reaction is carried out for 3 hours to obtain a pre-condensation intermediate. The temperature is further raised to 250° C., the vacuum degree is increased to 100 KPa, and the reaction is carried out for 2 hours to obtain the product with a molecular weight of 80,000 g / mol, a PDI of 5, and a terminal carboxyl group of 20 mol / t.

[0055] The preparation method of polyvinyl carbonate is as follows:

[0056] At 75°C and 0.6 MPa, CO2 and ethylene oxide were catalytically reacted in a solvent of dichloromethane for 15 hours to obtain the product with a molecular weight of 60,000 g / mol, a PDI of 4, and a Tg of 5°C.

[0057] In the present invention, the molecular weight and molecular weight distribution are obtained by GPC testing, and the detection method refers to 5.10 in GB / T31124-2014.

[0058] The propylene carbonate content is obtained by nuclear magnetic resonance testing; Tg is tested with reference to 5.9 in GB / T 31124-2014.

[0059] The terminal carboxyl group detection method refers to GB / T 14190-2017. The melt index detection method refers to GB / T 3682-2000, and the moisture detection method refers to 5.15 in GB / T 31124-2014.

[0060] In the present invention, the test standards for membrane permeability coefficient and selectivity refer to GB / T 1038.1-2022.

[0061] Example 1

[0062] 12g PPC-1, 3g PBAT, 0.05g compatibilizer ADR-4468, 0.08g antioxidant -168, and 0.08g anti-hydrolysis agent Stabaxol P200 were added to 95g DMF, stirred at 80°C for 0.5h, then heated to 140°C and stirred for 0.5h to obtain a uniform solution, which was allowed to stand for degassing for 0.5h. The degassed solution was poured onto a horizontal glass plate and spread evenly. The solvent was evaporated to obtain a primary membrane, and then the prepared primary membrane was vacuum dried to remove residual DMF. The drying temperature was 160°C and the drying time was 20min. Finally, a CO2 separation membrane with a thickness of 30μm was obtained. The membrane permeability coefficient and selectivity were tested. The CO2 separation membrane (25°C / 0.1MPa) had a CO2 permeability coefficient of 35880Bar, a CO2 / N2 selectivity of 13.6, and a breaking strength of 49MPa.

[0063] Example 2

[0064] 75 parts of PPC-1, 25 parts of PBAT, 0.3 parts of compatibilizer ADR-4468, 0.5 parts of antioxidant-168 and 0.5 parts of hydrolysis resistance agent Stabaxol P200 were blended and granulated in a twin-screw extruder at a processing temperature of 155°C (±5°C);

[0065] The blended modified particles were blown in a film blowing machine at a film blowing temperature of 160°C (±5°C) and a film thickness of 30 μm. Finally, a CO2 separation membrane was obtained with a CO2 permeability coefficient of 45850 Bar, a CO2 / N2 selectivity of 10.5 and a breaking strength of 40 MPa.

[0066] Example 3

[0067] 80 parts of PPC-1, 20 parts of PBAT, 0.3 parts of compatibilizer ADR-4468, 0.5 parts of antioxidant-168 and 0.5 parts of hydrolysis resistance agent Stabaxol P200 were blended and granulated in a twin-screw extruder at a processing temperature of 155°C (±5°C);

[0068] The blended modified particles were blown in a film blowing machine at a film blowing temperature of 160°C (±5°C) and a film thickness of 30 μm. Finally, a CO2 separation membrane was obtained with a CO2 permeability coefficient of 38680 Bar, a CO2 / N2 selectivity of 11.2, and a breaking strength of 38 MPa.

[0069] Example 4

[0070] 75 parts of PPC-1, 25 parts of PBAT, 0.3 parts of compatibilizer ADR-4468, 0.5 parts of antioxidant-168 and 0.5 parts of hydrolysis resistance agent were blended and granulated in a twin-screw extruder at a processing temperature of 155°C (±5°C);

[0071] The blended modified particles were cast into films at a casting temperature of 170°C (±5°C) and a film thickness of 30 μm. Finally, a CO2 separation membrane was obtained with a CO2 permeability coefficient of 40120 Bar, a CO2 / N2 selectivity of 10.4 and a breaking strength of 43 MPa.

[0072] Example 5

[0073] 90 parts of PPC-1, 10 parts of PBAT, 0.3 parts of compatibilizer ADR-4468, 0.5 parts of antioxidant-168 and 0.5 parts of hydrolysis resistance agent were blended and granulated in a twin-screw extruder at a processing temperature of 145°C (±5°C);

[0074] The blended modified particles were cast into films at a casting temperature of 160°C (±5°C) and a film thickness of 30 μm. Finally, a CO2 separation membrane was obtained with a CO2 permeability coefficient of 30250 Bar, a CO2 / N2 selectivity of 14.6 and a breaking strength of 29 MPa.

[0075] Example 6

[0076] 12g PPC-1, 4.6g PBAT, 0.05g compatibilizer ADR-4468, 0.08g antioxidant -168, and 0.08g anti-hydrolysis agent Stabaxol P200 were added to 95g DMF, stirred at 80°C for 0.5h, then heated to 140°C and stirred for 0.5h to obtain a uniform solution, which was allowed to stand for degassing for 0.5h. The degassed solution was poured onto a horizontal glass plate and spread evenly. The solvent was evaporated to obtain a primary membrane, and then the prepared primary membrane was vacuum dried to remove residual DMF. The drying temperature was 160°C and the drying time was 20min. Finally, a CO2 separation membrane with a thickness of 30μm was obtained. The membrane permeability coefficient and selectivity were tested. The CO2 separation membrane (25°C / 0.1MPa) had a CO2 permeability coefficient of 36100Bar, a CO2 / N2 selectivity of 13.6, and a breaking strength of 41MPa.

[0077] Example 7

[0078] The only difference from Example 1 is that PPC-1 is replaced by PPC-2 having a number average molecular weight Mn of 25,000 g / mol and a molecular weight distribution PDI of 5, and the rest is the same as Example 1.

[0079] The membrane permeability coefficient and selectivity were tested. The CO2 separation membrane (25℃ / 0.1MPa) had a CO2 permeability coefficient of 80530Bar, a CO2 / N2 selectivity of 5.6, and a breaking strength of 23MPa.

[0080] Example 8

[0081] The only difference from Example 2 is that the amounts of PPC-1 and PBAT used are 70 g PPC-1 and 30 g PBAT, respectively.

[0082] The membrane permeability coefficient and selectivity were tested. The CO2 separation membrane (25℃ / 0.1MPa) had a CO2 permeability coefficient of 46200Bar, a CO2 / N2 selectivity of 8.6, and a breaking strength of 40MPa.

[0083] Example 9

[0084] The only difference from Example 1 is that the amounts of PPC-1 and PBAT used are 12.5 g PPC-1 and 2.5 g PBAT, respectively.

[0085] The membrane permeability coefficient and selectivity were tested. The CO2 separation membrane (25℃ / 0.1MPa) had a CO2 permeability coefficient of 32300Bar, a CO2 / N2 selectivity of 11.8, and a breaking strength of 34MPa.

[0086] Example 10

[0087] 75 parts of PPC-3, 25 parts of PBAT, 0.3 parts of compatibilizer ADR-4468, 0.5 parts of antioxidant-168 and 0.5 parts of hydrolysis resistance agent Stabaxol P200 were blended and granulated in a twin-screw extruder at a processing temperature of 160°C (±5°C);

[0088] The blended modified particles were blown in a film blowing machine at a film blowing temperature of 165°C (±5°C) and a film thickness of 30 μm. Finally, a CO2 separation membrane was obtained with a CO2 permeability coefficient of 47580 Bar, a CO2 / N2 selectivity of 10.2 and a breaking strength of 37 MPa.

[0089] Embodiment 11

[0090] 12g PPC-4, 3g PBAT, 0.05g compatibilizer ADR-4468, 0.08g antioxidant -168, and 0.08g anti-hydrolysis agent Stabaxol P200 were added to 95g DMF, stirred at 80°C for 0.5h, then heated to 140°C and stirred for 0.5h to obtain a uniform solution, which was allowed to stand for degassing for 0.5h. The degassed solution was poured onto a horizontal glass plate and spread evenly. The solvent was evaporated to obtain a primary membrane, and then the prepared primary membrane was vacuum dried to remove residual DMF. The drying temperature was 160°C and the drying time was 20min. Finally, a CO2 separation membrane with a thickness of 30μm was obtained. The CO2 permeability coefficient of the CO2 separation membrane (25°C / 0.1MPa) was 32200Bar, the CO2 / N2 selectivity was 17.6, and the breaking strength was 53MPa.

[0091] Comparative Example 1

[0092] Pure PPC-1 particles were blown into film in a film blowing machine. It was found that pure PPC was difficult to form into film and the film was brittle and easy to break. Similar problems also occurred when other methods were used.

[0093] Comparative Example 2

[0094] The only difference from Example 1 is that PPC-1 is replaced by an equal amount of PBS (homemade).

[0095] The membrane permeability coefficient and selectivity were tested. The CO2 separation membrane (25℃ / 0.1MPa) had a CO2 permeability coefficient of 12350Bar, a CO2 / N2 selectivity of 12, and a breaking strength of 26MPa.

[0096] Comparative Example 3

[0097] The only difference from Example 1 is that PPC-1 is replaced by an equal amount of polyvinyl carbonate (prepared as above).

[0098] The membrane permeability coefficient and selectivity were tested. The CO2 separation membrane (25℃ / 0.1MPa) had a CO2 permeability coefficient of 15320Bar, a CO2 / N2 selectivity of 14, and a breaking strength of 22MPa.

[0099] Comparative Example 4

[0100] The only difference from Example 2 is that the amounts of PPC and PBAT are 60 parts of PPC and 40 parts of PBAT, respectively.

[0101] The membrane permeability coefficient and selectivity were tested. The CO2 separation membrane (25℃ / 0.1MPa) had a CO2 permeability coefficient of 65850Bar, a CO2 / N2 selectivity of 6.8, and a breaking strength of 42MPa.

[0102] Example 7 shows that when the molecular weight is lower than 30000 g / mol, the separation membrane is difficult to form, and even if it is formed, the strength is obviously weak. Example 8 shows that the mass ratio of PPC to PBAT is 2.3:1, which significantly reduces the selectivity of the separation membrane. Example 9 shows that the mass ratio of PPC to PBAT is 5:1, which reduces the membrane strength.

[0103] The PBS and polyvinyl carbonate used in Comparative Examples 2 and 3 both have crystallization phenomenon, which inhibits the carbon dioxide permeation rate. In addition, polyvinyl carbonate also has problems such as insufficient strength.

[0104] In Comparative Example 4, the PPC content was lower than 70%, and the separation selectivity decreased significantly.

[0105] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the CO2 separation membrane with high permeability coefficient and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A CO2 separation membrane with a high permeability coefficient, characterized in that: The raw materials for preparing the CO2 separation membrane include polypropylene carbonate and polybutylene adipate / terephthalate. Based on the total weight of the raw materials for preparing the CO2 separation membrane as 100%, the content of polypropylene carbonate accounts for 70-95wt%, and the content of polybutylene adipate / terephthalate accounts for 4-30%.

2. The high permeability CO2 separation membrane according to claim 1, characterized in that: The number average molecular weight Mn of the polypropylene carbonate is 30000-200000 g / mol; Preferably, the PDI of the polypropylene carbonate is 2 to 6; Preferably, the polypropylene carbonate has a propylene carbonate content of less than 2 wt %; Preferably, the glass transition temperature of the polypropylene carbonate is 24-36°C.

3. The high permeability CO2 separation membrane according to claim 1 or 2, characterized in that: The melt index of the polybutylene adipate / terephthalate at 190° C. and 2.16 kg is 3 to 5 g / 10 min; Preferably, the terminal carboxyl content of the polybutylene adipate / terephthalate is no more than 25 mol / t; Preferably, the water content of the polybutylene adipate / terephthalate is not more than 500 ppm.

4. The high permeability CO2 separation membrane according to any one of claims 1 to 3, characterized in that The weight ratio of the polypropylene carbonate to polybutylene adipate / terephthalate is 2.5-4:

1.

5. The high permeability CO2 separation membrane according to any one of claims 1 to 4, characterized in that The raw material for preparing the CO2 separation membrane further includes at least one of an optional compatibilizer, an optional antioxidant or an optional anti-hydrolysis agent; Preferably, the compatibilizer includes but is not limited to one or a combination of at least two of ADR-4468, ADR-4368 or ADR-4385; Preferably, the antioxidant includes but is not limited to one or a combination of at least two of antioxidant-1010, antioxidant-1076, antioxidant-168, antioxidant-B215 or antioxidant-B245; Preferably, the anti-hydrolysis agent includes but is not limited to one or a combination of at least two of Stabaxol I, Stabaxol P100 or Stabaxol P200; Preferably, the raw materials for preparing the high permeability CO2 separation membrane include the following components in weight percentage: 70-95 wt% of polypropylene carbonate, 4-30 wt% of polybutylene adipate / terephthalate, 0.1-2 wt% of a compatibilizer, 0.1-1.5 wt% of an antioxidant, and 0.1-1 wt% of an anti-hydrolysis agent.

6. The high permeability CO2 separation membrane according to any one of claims 1 to 5, characterized in that The thickness of the high permeability CO2 separation membrane is 30 to 100 μm.

7. The method for preparing a CO2 separation membrane with a high permeability coefficient according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: Dissolving polypropylene carbonate, polybutylene adipate / terephthalate, an optional compatibilizer, an optional antioxidant, and an optional anti-hydrolysis agent in a solvent to obtain a solution, and coating the solution to form a film to obtain the CO2 separation membrane with a high permeability coefficient; Preferably, the concentration of the solution is 5 to 15 wt%; Preferably, the solvent is selected from any one of N,N-dimethylformamide, dichloromethane, acetone, toluene or dimethyl sulfoxide, or a combination of at least two thereof.

8. The method for preparing a CO2 separation membrane with a high permeability coefficient according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: Mixing polypropylene carbonate, polybutylene adipate / terephthalate, an optional compatibilizer, an optional antioxidant and an optional anti-hydrolysis agent, melt-extruding and granulating, and then blowing a film to obtain the CO2 separation membrane with a high permeability coefficient; Preferably, the processing temperature of the melt extrusion is 135-170°C; Preferably, the temperature of the film blowing is 130-170°C.

9. The method for preparing a CO2 separation membrane having a high permeability coefficient according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: Mixing polypropylene carbonate, polybutylene adipate / terephthalate, an optional compatibilizer, an optional antioxidant and an optional anti-hydrolysis agent, melt-extruding and granulating, and then casting or stretching to obtain the CO2 separation membrane with a high permeability coefficient; Preferably, the processing temperature of the melt extrusion is 135-170°C; Preferably, the film-casting is carried out in a tape-casting machine; Preferably, the temperature of the film casting is 150-180°C.

10. Use of the high permeability CO2 separation membrane according to any one of claims 1 to 6 in CO2 capture and recovery.

Citation Information

Patent Citations

  • Polypropylene carbonate and preparation method thereof

    CN113185684A

  • Cross-lined polymethyl ethylene carbonate polymer electrolyte membrane and preparation method thereof

    CN101200554A

  • Method for preparing high-permeability polydimethylsiloxane gas separation membrane and application thereof

    CN102806024A

  • Modified chain extender as well as preparation method and application thereof

    CN112876646A

  • Light-driven single-layer Janus oil-water separation membrane and preparation method thereof

    CN115646221A

Cited By

  • Hybrid membrane material for separation and removal of carbon dioxide in water and its preparation method and application

    CN122786893A